AB0515 Skin manifestations as independent predictors and the initial risk faktors for systemic antiphospholipid events. (15th June 2017) - Stojanovich, L; Djokovic, A; Stanisavljevic, N; Zdravkovic, M
Abstract : Background: Antiphospholipid syndrome (APS) patients express skin manifestations with the presence of various levels of antiphospholipid antibodies (aPL).Several studies have shown the frequency of dermatological manifestations with APS 1, 2, 3, including livedo reticularis, cutaneous ulcers, acrocyanosis, and other. Objectives: Dermatological manifestations can be the initial clue in the diagnosis of this disease. Methods: Our study includes a total of 508 APS patients; 360 were PAPS patients (283 female and 77 male, mean age 44.0±12.9 years), 148 had APS associated with SLE/SAPS (133 female and 15 male, mean age 47.7±14.8 years).aPL analysis included:LA, aCL (IgG/IgM), β2 GPI (IgG/IgM).In all patients, we collected data considering frequently occured skin lesions. Results: Our results showed prevalence of skin manifestations in SAPS group of patinenst regading to PAPS (Table 1 ). Patients with skin manifestations overall had higher prevalence of thrombosis (Table 2 ). Conclusions: Dermatological manifestations can be very often the initial symptoms of severe manifestations of APS.Our study showed that patients with secondary APS had higher prevalence of skin lesions, and that some aPL types were risk factors for thrombotic manifestations in APS patients References: Toubi E, Krause I, Fraser A, Lev S, Stojanovich L, Rovensky J, et al. Livedo reticularis is a marker for predicting multi-system thrombosis in antiphospholipid syndrome. Clin Exp Rheumatol 2005;23:499–504. Weinstein S, Piette W. Cutaneous manifestations of antiphospholipid antibody syndrome. Hematol Oncol Clin North Am 2008;22:67–77. Asherson RA, Cervera R, Klumb E, Stojanovich L. et all.: Amputation of Digits or Limbs in Patients with Antiphospholipid Syndrome. 21 January 2008. Seminars in Arthritis and Rheumatism. 2008; 38: 124–31. Stojanovich L, Markovic O, Marisavljevic D et all. Influence of antiphospholipid antibody levels and type on thrombotic manifestations: results from the Serbian National cohort study. Lupus 2011;0: 1–8. Stojanovich L, Kontic M, Djokovic Aet all. Association between Systemic Non-criteria APS Manifestations and Antibody Type and Level: Results from the Serbian National Cohort Study. Clinical and Experimental Rheumatology, 2013, 31(5):756–60. Acknowledgements: This work was supported by research grant number 175041 for 2011 - 2017, issued by the Ministry of Science of the Republic of Serbia. Disclosure of Interest: None declared